2015
DOI: 10.1063/1.4904270
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of piezoelectric ZnO/AlN−stacked flexible nanogenerators for energy harvesting applications

Abstract: Flexible piezoelectric zinc oxide (ZnO)-based nanogenerators (NGs) using an aluminum nitride (AlN) interlayer are proposed for high-efficiency energy harvesting applications. The effects of the AlN interlayer on device performance are studied. Use of the AlN interlayer in ZnO-based vertically integrated NGs (VINGs) results in a significant improvement in terms of the magnitude of the output voltages of up to 200 times when compared with a ZnO-based VING without any AlN interlayer. The improved device energy co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 23 publications
0
30
0
Order By: Relevance
“…The piezoelectric effect is a linear electromechanical interaction in insulating crystalline materials without inversion symmetry . Piezoelectric materials have extensive applications in the electronic, energy, and medical fields, such as sensors, actuators self‐power sources, and low‐power logic switches . In‐plane piezoelectricity has been obtained in a series of 2D materials, including h‐BN, MX 2 , and NX monolayers .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…The piezoelectric effect is a linear electromechanical interaction in insulating crystalline materials without inversion symmetry . Piezoelectric materials have extensive applications in the electronic, energy, and medical fields, such as sensors, actuators self‐power sources, and low‐power logic switches . In‐plane piezoelectricity has been obtained in a series of 2D materials, including h‐BN, MX 2 , and NX monolayers .…”
Section: Electronic Propertiesmentioning
confidence: 99%
“…Some research teams have used insulators or other semiconductor materials to form a good potential barrier to increase output voltages [19]. Other research using AlN or various oxides (MoO x , Cu 2 O, and NiO) has been reported [14,16,18,20]. Despite such intensive research, only few studies were published using SiO 2 as an insulator [21].…”
Section: Introductionmentioning
confidence: 99%
“…Their fabrication seems to be cost-effective because all that is required to fabricate these micro-energy generators is simply the stacking of thin film layers. Similarly, high-efficiency piezoelectric ZnO-based nanogenerators have also been developed for energy harvesting applications by forming ZnO/AlN-stacked layers [14] and adopting free-carrier-modulated ZnO:N piezoelectric thin films [15]. Moreover, there have been attempts to improve the piezoelectric materials or the device performance by adopting new electrodes or forming a p-n junction to block the screening effect based on energy band considerations [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…ZnO is one of the most favorable materials widely used in electronics (transistors) [4,5], sensors [6][7][8], catalysts [9][10][11], light emitting devices [12][13][14][15], piezoelectric devices [16][17][18][19][20], solar cells [21][22][23], sunscreens [24,25], lasers diodes [26,27], hydrophobic surfaces [28,29], magnetic data storage [30,31], water disinfection [32], antiviral agent [33,34], anti-cancer agent [35], hazardous waste remediation [36], flexible plastic devices [37], degradation of pollutants [38], energy conversion and storage devices [22,[39][40][41]. ZnO is a wide band gap semiconductor (3.3 eV) with a high excitation binding energy of 60meV [42] at room temperature.…”
mentioning
confidence: 99%